Pengembangan Media Pembelajaran Matematika Berbasis Aplikasi Android Menggunakan Power Point dan iSpring pada Materi Himpunan untuk Siswa Kelas VII SMP Swasta Swadaya Tarus - Dethan, Sergius; Samo, Damianus Dao; Blegur, Irna Karlina Sensiana (Griya Journal of Mathematics Education and Application, 2024)
The number of smartphone users is increasing across various demographics, including students. With the presence of smartphones among students, it should be able to assist learners in enhancing their interest and understanding of mathematics effectively, anytime and anywhere. Therefore, this research aims to develop a mathematics learning media based on an Android application using PowerPoint and iSpring for set theory material for Grade VII students at Swadaya Tarus Private Junior High School that is valid, practical, and effective. The method employed in this research is research and development using the ADDIE development model: Analysis, Design, Development, Implementation, and Evaluation. Data for this research were obtained through interviews, questionnaires, and tests. The results of this research show that the set theory class application meets the criteria for valid, practical, and effective learning media for set theory material. The average total validity score from three validators is 4.34, indicating that the Android-based mathematics learning media falls into the valid category. The average practicality score from the large class teacher is 4.38, and the responses from the small-scale trial students were 4.6, while the responses from the large-scale trial students were 4.67, placing the Android-based mathematics learning media in the practical category. Additionally, the pass rate for small-scale trial students was 80%, and the pass rate for the large-scale trial students was 70%, indicating that the developed Android-based mathematics learning media falls into the effective category.